2015
DOI: 10.1152/ajplung.00176.2014
|View full text |Cite
|
Sign up to set email alerts
|

Mouse lung development and NOX1 induction during hyperoxia are developmentally regulated and mitochondrial ROS dependent

Abstract: Animal models demonstrate that exposure to supraphysiological oxygen during the neonatal period compromises both lung and pulmonary vascular development, resulting in a phenotype comparable to bronchopulmonary dysplasia (BPD). Our prior work in murine models identified postnatal maturation of antioxidant enzyme capacities as well as developmental regulation of mitochondrial oxidative stress in hyperoxia. We hypothesize that consequences of hyperoxia may also be developmentally regulated and mitochondrial react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 47 publications
3
58
0
Order By: Relevance
“…The exact source of mROS may change with the mitochondrial stressor and particular disease state, but investigations into the source of mROS in many lung diseases is limited by the lack of highly specific in vivo mROS-sensing agents (103). That said, there is compelling evidence for a role of mROS in the pathogenesis of a number of lung diseases, including PF (54), COPD (20,50), asthma (104), CF (105), lung cancer (106), BPD (107), and PH (108).…”
Section: Mitochondrial Transcription Factormentioning
confidence: 99%
“…The exact source of mROS may change with the mitochondrial stressor and particular disease state, but investigations into the source of mROS in many lung diseases is limited by the lack of highly specific in vivo mROS-sensing agents (103). That said, there is compelling evidence for a role of mROS in the pathogenesis of a number of lung diseases, including PF (54), COPD (20,50), asthma (104), CF (105), lung cancer (106), BPD (107), and PH (108).…”
Section: Mitochondrial Transcription Factormentioning
confidence: 99%
“…Indeed, the transmission of mtDNA mutations occurs in one in every 200 newborns, which potentially may cause disease or increase disease susceptibility (Elliott et al , ). Treatment with a mitochondria‐specific antioxidant, mitoTEMPO, during early post‐natal hyperoxia protected against compromised alveolarization (Datta et al , ), which suggests that targeted antioxidant therapy could be used to prevent or treat BPD. Hyperoxic exposure induces UCP2 expression in pulmonary macrophages and enhanced UCP3 levels in skeletal muscles in mice (Flandin et al , ; Steer et al , ), which may be compensatory responses to increased oxidative stress and mtROS.…”
Section: Mitochondrial Dysfunction In Chronic Lung Diseasesmentioning
confidence: 99%
“…We have previously shown that mice exposed to this model have evidence of increased oxidative stress and that a mitochondrially-targeted antioxidant can prevent end organ damage in the lung and cardiovascular system [16, 81]. The NOX family is considered an important source of ROS in blood vessels and has been shown to be important in the pathogenesis of retinal angiogenesis and ischemic retinopathies [27].…”
Section: Discussionmentioning
confidence: 99%